الكتابة الغرافيتية والقانون السوسيولساني - بولعراس، الجمعي محمود (جامعة قاصدي مرباح - ورقلة, 2015)
There is no doubt that social conditions is contained in language, in the various political and cultural orientations, etc., . And that the relationship between this contexts is solid. This is what socio-Linguistics tried to study, through the convergence of systematic scientific meeting and Linguistics. Hence, this study is trying to highlight to a phenomenon which prominent on the surface today, it is frequency of phrases deviant in the socio-linguistic fabric, in terms of quantity and quality, which infect the Arabic language contemporary , so, we indicate a serious indicator in the speech paths, especially in representing vocabulary, and contemporary Arabic texts, to developments in the political, cultural and contemporary social fields, which called for scientists to consider: - Is social action resulting from the linguistic reasons?
لا ريب في أن الأوضاع الاجتماعية بمختلف مشاربها السياسية والثقافية وغيرها تضمنتها اللغة، وأن العلاقة بين السياقين متين، وهذا ما حاولت اللسانيات الاجتماعية بلورته من خلال التقارب المنهجي لعلمي الاجتماع واللسانيات، ومن هنا فمداخلتنا تحاول أن تبرز ظاهرة بارزة على السطح اليوم وهي ظاهرة تواتر العبارات المنحرفة في النسيج اللساني الاجتماعي من حيث الكم والنوع التي تصيب اللغة العربية المعاصرة، وتدلل إلى مؤشر خطير في مسارات الكلام، وبخاصة في تمثّل مفردات ونصوص اللغة العربية المعاصرة للمستجدات السياسية والثقافية والاجتماعية المعاصرة، الأمر الذي دعا العلماء إلى النظر في : هل الفعل الاجتماعي ناتج عن مستحثات اللغة؟
Keywords: اللسانيات الاجتماعية -- الكتابة الغرافيتية -- القانون السوسيولساني -- الجوانب اللغوية -- القيم الأخلاقية